การวิเคราะห์ต้นทุนโลจิสติกส์ในอุตสาหกรรอิเล็กทรอนิกส์ด้วยเทคนิคการวิเคราะห์ต้นทุนฐานกิจกรรมด้วยเกณฑ์เวลา - หทัยกานต์ ปะระดี (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2017)
Logistics Cost Analysis in Electronics Industries with Time- Driven Activity-Based Costing Technique aims to analyze logistics cost structure in the electronic industry and analyze the impact of logistics cost for electronics industry perspective ASEAN Economic Community or AEC. Logistics cost analysis used Time-Driven Activity-Based Costing (TD-ABC) is tool. TD-ABC analysis used them as a primary cost driver and it indicate incurred cost in each activity which based on 4 logistics activities procurement, inventory holding, warehousing, and transportation. Then, used to supply chain redesign strategy such as redesign the roles and processes in the supply chain, reduce lead times and update data, and synchronize all logistics processes to customer demand etc. analyzes impact of logistics cost of the electronics industry. The results found that the highest cost in sample electronic industry is inventory holding cost with 59.08 percent of logistics cost. Then, following by transportation cost (26.60 percent) and warehousing cost (8.57 percent). Conversely, the least cost is the procurement cost (5.76 percent). The effective of logistics cost is affected supply chain redesign, which is the sample off-shoring toward Singapore Malaysia and Indonesia. They are impact to increasing of logistics cost ratio about 185.00%, 5.30%, and 16.51% of logistics cost, respectively. Conversely, the logistics cost ratio are decreasing about 13.41% and 4.28% of logistics cost when they off-shoring toward Vietnam and Philippines, respectively. Finally, the data of this study apply to the operation, planning, financial, and management which is used in the organization. Furthermore, the accurate data of cost planning in the future for supply chain management strategy and both macro logistics and micro logistics.